Effectiveness of the Government Internal Supervision Apparatus (APIP) in Agency "A" - Zahratul Husna; Purwatiningsih Lisdiono (Jurnal Indonesia Sosial Teknologi, 2025)
Supervision is the most important element in a management system in government. One of the main factors that can support the successful implementation of control is the effectiveness of the role of the government's internal supervisory apparatus (APIP). This study aims to evaluate the effectiveness of the government's internal supervisory apparatus based on three factors consisting of the audit environment or position (management support, Independence, Objectivity), audit implementers (Skills, Human Resources Development), and audit processes (Quality control, Activity planning, Activity coordination, Scope of work, Implementation of activities, and Communication of results) using the Professional Standards of Internal Audit Practice (International Professional) Practices Framework – IPPF) issued by The Institute of Internal Auditors (IIA). This research is a case study with a qualitative approach and data triangulation method obtained from interviews, documentation, and observation. The results of the study show that from the environment/position of APIP agency A, there are still several points that are not effective, such as limited human resource support and a non-independent organizational/reporting structure. The skills and competence of audit implementers can be said to be effective, but except for inadequate auditors, it is not proportional to the scope that must be done so the audit assignment is not optimal and there are still some audit processes that are not comprehensive. The results of this study are expected to provide input to relevant agencies to be considered in improving the institution of government internal supervision apparatus so that they can realize effective APIP.